Studi Komparatif Lukisan Perempuan Perupa dengan Pria Perupa Impresionis dalam Tema Kehidupan Keseharian - Ira Adriati Winarno; Agus Sachari (Journal of Visual Art and Design, 2008)
Impressionism is an art movement that firstly established in France in the middle of 19th century. Claude Monet, Ãˆdouard Manet, Pierre-Auguste Renoir, and Edgar Degas are famous male impressionist artists that were known by many, yet there are famous female impressionist artists such as Berthe Morisot, Mary Cassatt, Eva Gonzales, and Marie Bracquemond that deserve to be known as well. The presented paper discusses the aesthetics value and meanings of paintings of these female impressionist artists, through the perspective of art criticism, historical method, and women studies. Object of analysis are paintings that depicting domestic life made by mentioned artists above. Results show that the depicted domestic life in those paintings presented a unique gaze of a woman, as shown in the representation of body language to express the relationship between mother and children. Thus, female impressionist paintings emphasize more on the activities and aspiration of women than the beauty of their bodies. The painted theme shows that the artists express gender equality and/or independent (or self-supporting) women, which are presented in an equal aesthetic quality compared to those of male impressionist artists.